THE INFLUENCE OF SOCIETY TO THE STUDENTS SKILL IN ENGLISH TO THE SECOND YEAR STUDENT OF SMPN 5 TANDUN - Vera Vianti Mala (JEE (Journal of English Education), 2019)
The pupose of this research is carried out in order to find out how far the influence of society to the students skills in English to the second year students of SMPN 5 Tandun in 2018/2019 academic year is. The library research is applied based on the needs of the books as the sources of the theories and informations, and the field research is applied on the need ofdata from the field, in this case from SMPN 5 Tandun. As the instrument for collection the data, the writer uses test. After getting the data, the next step which is done by the writer is analizing it by using the statistical analysis. The students‟ skill English are also influenced by other factors, like the students‟ motivation, interest, aptitute, the method applied by the teachers in teaching, the school facilities, the family factor, etc. After finishing collecting and analyzing the data it has been known that there is a significant influence of society to the students‟ skill to the second year students of SMPN 5 Tandun. It means that the hypothesis of this research is accepted.